Open and distance learning (ODL) prospects and challenges the case of University of Zamboanga - Knuttel, Sven Heinrich B. (Universidad de Zamboanga Journal : Official Peer Reviewed Journal Publication, 2013)
Abstract: Research study is about prospects and challenges of open and distance learning (ODL), which is a way of combining work and family responsibilities with educational opportunities, in Universidad de Zamboanga (UZ). Presented in this study is the mode, Learning management system (LMS), readiness of the faculty, and infrastructure/facilities to consider for ODL. Descriptive-qualitative method was used. Data gathering was done at Universidad de Zamboanga: City Campus, J.S. Alano Street and Main Campus, Don Toribio Street Tetuan, Zamboanga City; MSU-IIT, Iligan City; and UPOU, Los Baños, Laguna. Data gathering was primarily through schedule interview for the curriculum specialist, key informants, and questionnaire for instructors of UZ. Treatment of data was done through coding and documents analysis. As shown in the study the mode suited for ODL is blended learning. The LMS are moodle, Google apps for education and blackboard with UZ's faculty readiness with 70.5%. A number of robust internet service providers (ISP), server hosting, backup power & backup servers, and module developers should be the focus of infrastructure of ODL. The mode of ODL suited for the UZ is blended learning. Combination of google apps for education and Moodle is recommended for LMS. Intense trainings, workshops and seminars on ODL for the teachers are also suggested by the researcher.